2023
DOI: 10.14218/jcth.2022.00392
|View full text |Cite
|
Sign up to set email alerts
|

IGF2-NR4A2 Signaling Regulates Macrophage Subtypes to Attenuate Liver Cirrhosis

Abstract: Background and Aims: Liver cirrhosis can lead to liver failure and eventually death. Macrophages are the main contrib-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…BMI1 [378], IGF2 [379], PRKCB (protein kinase C beta) [380], CCL5 [381], E2F1 [382], PF4 [111], CYP11B2 [383], WNT3A [384], COMP (cartilage oligomeric matrix protein) [385], DES (desmin) [335], ANGPTL3 [386], CYP3A5 [387], LRP2 [388], PAH (phenylalanine hydroxylase) [389], HMGCS2 [390], AGXT2 [391], FABP1 [392], CUBN (cubilin) [393], DIO1 [394], MIOX (myo-inositol oxygenase) [344], FGF1 [395], CRY1 [396], PPARGC1A [397], CYP2C8 [398], GC (GC vitamin D binding protein) [399], VNN1 [350], NOX4 [400], EPHX2 [401], F11 [402], AQP2 [403], NAT8 [404], CLDN2 [405], EGF (epidermal growth factor) [406], ANGPT1 [174], CLCN5 [407], KL (klotho) [176], DEFB1 [408], ACE2 [409], NR4A1 [410], SLC13A3 [411], CADM1 [412], AZGP1 [367], DPP4 [413], REN (renin) [414], ABCB1 [415], CCR1 [416], MANBA (mannosidase beta) [417], SELP (selectin P) [418], CLDN16 [419], F8 [420], VCAM1 [421], PLD1 [422], SLCO4C1 [423], TINAG (tubulointerstitial nephritis antigen) [424], SULT1C2 [425], PLAT (plasminogen activator, tissue type) [426] and ALB (albumin) [427] can participate in the occurrence and development of chronic kidney disease. IGF2 [428], SCARNA10 [429], IRF7 [430], PRKCB (protein kinase C beta) [431], CCL5 [432], E2F1 [433], PF4 [434], HOXC8 [435], SMPD3 [118], GREM1 [436], WNT3A [437], COMP (cartilage oligomeric matrix protein) [438], FLI1 [439], DES (desmin) [440], BHMT (betaine--homocysteine ...…”
Section: Discussionmentioning
confidence: 99%
“…BMI1 [378], IGF2 [379], PRKCB (protein kinase C beta) [380], CCL5 [381], E2F1 [382], PF4 [111], CYP11B2 [383], WNT3A [384], COMP (cartilage oligomeric matrix protein) [385], DES (desmin) [335], ANGPTL3 [386], CYP3A5 [387], LRP2 [388], PAH (phenylalanine hydroxylase) [389], HMGCS2 [390], AGXT2 [391], FABP1 [392], CUBN (cubilin) [393], DIO1 [394], MIOX (myo-inositol oxygenase) [344], FGF1 [395], CRY1 [396], PPARGC1A [397], CYP2C8 [398], GC (GC vitamin D binding protein) [399], VNN1 [350], NOX4 [400], EPHX2 [401], F11 [402], AQP2 [403], NAT8 [404], CLDN2 [405], EGF (epidermal growth factor) [406], ANGPT1 [174], CLCN5 [407], KL (klotho) [176], DEFB1 [408], ACE2 [409], NR4A1 [410], SLC13A3 [411], CADM1 [412], AZGP1 [367], DPP4 [413], REN (renin) [414], ABCB1 [415], CCR1 [416], MANBA (mannosidase beta) [417], SELP (selectin P) [418], CLDN16 [419], F8 [420], VCAM1 [421], PLD1 [422], SLCO4C1 [423], TINAG (tubulointerstitial nephritis antigen) [424], SULT1C2 [425], PLAT (plasminogen activator, tissue type) [426] and ALB (albumin) [427] can participate in the occurrence and development of chronic kidney disease. IGF2 [428], SCARNA10 [429], IRF7 [430], PRKCB (protein kinase C beta) [431], CCL5 [432], E2F1 [433], PF4 [434], HOXC8 [435], SMPD3 [118], GREM1 [436], WNT3A [437], COMP (cartilage oligomeric matrix protein) [438], FLI1 [439], DES (desmin) [440], BHMT (betaine--homocysteine ...…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are key enzymes involved in the degradation and deposition of all proteins in the extracellular matrix and play an important role in the process of tissue remodeling and fibrosis. 14 Huang et al 15 suggested that matrix metalloproteinase-7 (MMP-7) was overexpressed in liver biopsy samples and there was a significant difference when comparing the control group (children with no liver diseases) and the liver transplantation group among children with BA. Lertudomphonwanit et al 16 found that MMP-7 is also highly expressed in the sera of patients with BA, through large-scale, quantitative serum proteomics.…”
Section: Mmp-7mentioning
confidence: 99%
“…IGF2 plays an important role in immune homeostasis and inflammatory response caused by antigen presence (42,(82)(83)(84). This growth factor has a direct effect on immune cells such as macrophages, inhibiting the inflammatory response at low doses (42).…”
mentioning
confidence: 99%